2019
DOI: 10.1111/1742-6723.13375
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome and management pathways for adult patients presenting to an Australian health service with distal radius fracture

Abstract: Objective Primarily to determine mid‐term functional outcome for patients with distal radius fracture (DRF) and to compare this between operative and conservatively managed patients. Secondarily to examine for differences in age, gender and number of instability factors between management groups. Methods Eligible patients (age 18 years or more, closed DRF managed to completion of care within Monash Health), presenting between 1 January and 31 December 2016. Completion of the patient‐rated wrist evaluation (PRW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“… 30 Another retrospective study reported excellent functional results in 67% of operatively treated patients, 5 and in a study of mid-term (6–12 months post-injury) functional outcome in adult patients with DRF between operative and non-operative treatment, no significant difference was found between operative and non-operative groups. 31 The main results of the previous studies are summarized in Supplemental Table S2 . Both operatively and non-operatively treated patients managed well at a minimum of four years after DRF in the present analyses.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Another retrospective study reported excellent functional results in 67% of operatively treated patients, 5 and in a study of mid-term (6–12 months post-injury) functional outcome in adult patients with DRF between operative and non-operative treatment, no significant difference was found between operative and non-operative groups. 31 The main results of the previous studies are summarized in Supplemental Table S2 . Both operatively and non-operatively treated patients managed well at a minimum of four years after DRF in the present analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies with comparable age groups to those of cohorts 1 and 2 have shown to have a good correlation in patientrated wrist evaluation (PRWE) in nonoperative when compared with operative management. 15 In their recent guidelines, the BOA and BSSH outline ulnar variance and dorsal tilt as the most important radiological parameters in extra-articular fractures, with the addition of an intra-articular step for intra-articular fractures. Our data analysis has dorsal tilt being the parameter that most often met the guideline's "threshold for intervention."…”
Section: Discussionmentioning
confidence: 99%